Australian Universities, Indigenization, Whiteness, and Settler Colonial Epistemic Violence - B Bennett; K Menzel; Jacob Prehn; TG Gates (2023)
This chapter argues that despite numerous strategies, reports, and scholarship, Australian universities are still largely based on White Western worldviews and as a result continue to perpetrate and perpetuate settler colonial epistemic violence. To overcome the current settler colonial epistemic violence exerted by tertiary education providers, genuine relationships with First Nation peoples and communities need to be established, and space must be made for these communities to speak for themselves within the academy. Universities and governments should follow by providing appropriate allocation of resources for the indigenization of curricula and governance structures, within faculties and campuses. If this is achieved, the Australian tertiary education sector will become an international leader by deconstructing Whiteness, providing a greater educational experience, and exposing graduates to multiple worldviews. We address social work as a discipline and suggest ways forward.